2020
DOI: 10.1016/j.molmet.2020.101082
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged fasting drives a program of metabolic inflammation in human adipose tissue

Abstract: Objective The human adaptive fasting response enables survival during periods of caloric deprivation. A crucial component of the fasting response is the shift from glucose metabolism to utilization of lipids, underscoring the importance of adipose tissue as the central lipid-storing organ. The objective of this study was to investigate the response of adipose tissue to a prolonged fast in humans. Methods We performed RNA sequencing of subcutaneous adipose tissue samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 34 publications
2
12
0
Order By: Relevance
“…CRP, which increased in response to high-calorie feeding, also increased in response to fasting (median increase: 100% [38.3%, 277.0%], P = 0.0003), and GDF15, another inflammatory marker, also increased in response to fasting ( P = 0.0005; Table 2 ). These findings are consistent with the increased inflammatory response observed in prolonged human fasting ( 16 ). Changes in adipokines, bone turnover markers, or inflammatory markers did not predict changes in BMAT during the fasting visit ( Supplemental Table 8 ).…”
Section: Resultssupporting
confidence: 90%
“…CRP, which increased in response to high-calorie feeding, also increased in response to fasting (median increase: 100% [38.3%, 277.0%], P = 0.0003), and GDF15, another inflammatory marker, also increased in response to fasting ( P = 0.0005; Table 2 ). These findings are consistent with the increased inflammatory response observed in prolonged human fasting ( 16 ). Changes in adipokines, bone turnover markers, or inflammatory markers did not predict changes in BMAT during the fasting visit ( Supplemental Table 8 ).…”
Section: Resultssupporting
confidence: 90%
“…In humans, a prolonged 10-day fast results in transcriptomic signatures of increased lipolysis/lipid metabolism and reduced activation of pathways related to glycolysis and oxidative phosphorylation. Interestingly, this prolonged fasting period also contributes to the upregulation of inflammatory pathways and macrophage activation in subcutaneous fat tissue ( 42 ), reflecting a potential hormesis response and downstream protective mechanisms. Another study showed that short-term fasting is associated with enrichment of transcriptomic pathways involved in fatty acid oxidation, cell cycling and apoptosis, and a decrease in the expression of pro-inflammatory genes in peripheral blood mononuclear cells ( 16 ).…”
Section: Alternate Day Fasting and Prolonged Fastingmentioning
confidence: 99%
“…Surprisingly, the median HOMA-IR, which was 1.4 at baseline and trending downward after fasting (1.1), had more than doubled after refeeding (3.1), suggesting that fasting may increase insulin resistance upon refeeding, at least in this overweight/obese non-diabetic population. Indeed, prolonged fasting may result in temporary physiological changes, such as downregulation of insulin receptor expression [ 45 ], elevated VLDL and TG levels [ 16 , 46 ], and metabolic inflammation in adipose tissue [ 47 ], which could temporarily affect insulin sensitivity during refeeding. We speculate that the observed insulin resistance is a temporary, rebound phenomenon caused by a reversal of the metabolic switch from ketosis back to glycolysis upon refeeding.…”
Section: Discussionmentioning
confidence: 99%